1994
DOI: 10.1007/bf02260938
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial enzyme deficiencies in Down's syndrome

Abstract: Defects in cytochrome oxidase (CO; complex 4) have recently been demonstrated in blood platelets and in brain tissue from patients with Alzheimer's disease (AD) with possible etiological implications. Because of pathogenetic similarities with AD, we have measured the activities of several mitochondrially localised enzymes in the blood platelets of individuals afflicted with trisomy-21 (Down's syndrome). The activities of monoamine oxidase, cytochrome oxidase, isocitrate dehydrogenase, and glutamate dehydrogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…However, we have previously reported that there is a high correlation between white blood cell MAO-B activity and trbc MAO activity (r = 0.98; n = 20). 32 Therefore, we used nuclear extracts from human white blood cells to perform gel-shift analyses of the occurrence of proteins that bind to the 0.15-kb sequence of the MAOB promoter. Samples were obtained from male, non-smoking volunteers selected for a wide spread of trbc MAO activity.…”
Section: Transcriptional Regulation Of Trbc Maomentioning
confidence: 99%
“…However, we have previously reported that there is a high correlation between white blood cell MAO-B activity and trbc MAO activity (r = 0.98; n = 20). 32 Therefore, we used nuclear extracts from human white blood cells to perform gel-shift analyses of the occurrence of proteins that bind to the 0.15-kb sequence of the MAOB promoter. Samples were obtained from male, non-smoking volunteers selected for a wide spread of trbc MAO activity.…”
Section: Transcriptional Regulation Of Trbc Maomentioning
confidence: 99%
“…COX dysfunction also increases free radicals, reduces energy stores, and disturbs amyloid metabolism (Gabuzda et al, 1994;Mutisya et al, 1994;Smith et al, 1996;Davis et al, 1997). COX dysfunction is associated with Down's syndrome; many Down's syndrome patients develop AD (Prince et al, 1994;Busciglio and Yanker, 1995). Mutations in mitochondrial COX genes also seem to segregate with late-onset AD .…”
mentioning
confidence: 99%
“…Therefore, in this syndrome, the metabolism is down-regulated by lowered basal metabolic rate [20][21][22]. Our study shows a relationship between lack of ER XbaI site and obesity in both genders.…”
Section: Discussionmentioning
confidence: 76%